KARAKTERISTIK KIMIA DAN MUTU SENSORI BAKSO IKAN PATIN DENGAN PENGGUNAAN TEPUNG BONGGOL PISANG DAN TAPIOKA - Daniel Chandra Manurung; Usman Pato; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Meatballs is a processed meat product that is very popular among people. This study was aimed to obtain the best ratio of banana excrescence flour and tapioca on the quality of patin fish meatballs.This research was conducted by using Completely Randomized Design (CRD) experiment with five treatments and three replications. The data were analyzed by ANOVA followed by Duncan’s New Multiple Range Test (DNMRT) at 5% level. The treatments in this research were P1 (ratio banana excrescence flour and tapioca 0:3), P2 (ratio banana excrescence flour and tapioca 1:2), P3 (ratio banana excrescence flour and tapioca 1:1), P4 (ratio banana excrescence flour and tapioca 2:1), and P5 (ratio banana excrescence flour and tapioca 3:0). The results analysisof variance show that ratio of the banana excrescence flour and tapioca significantly affected themoisture, ash, fiber, fat and protein contentsas well as sensory evaluation of meatballs. The best formulations was obtained on the meatballs are P2 with ratio banana excrescence flour and tapioca 1:2 which had a moisture content 68.34%, ash content 1.93%, fat content 0.81%, fiber content of 1.51% and protein content 12. 92%.Meatballs is a processed meat product that is very popular among people. This study was aimed to obtain the best ratio of banana excrescence flour and tapioca on the quality of patin fish meatballs.This research was conducted by using Completely Randomized Design (CRD) experiment with five treatments and three replications. The data were analyzed by ANOVA followed by Duncan’s New Multiple Range Test (DNMRT) at 5% level. The treatments in this research were P1 (ratio banana excrescence flour and tapioca 0:3), P2 (ratio banana excrescence flour and tapioca 1:2), P3 (ratio banana excrescence flour and tapioca 1:1), P4 (ratio banana excrescence flour and tapioca 2:1), and P5 (ratio banana excrescence flour and tapioca 3:0). The results analysisof variance show that ratio of the banana excrescence flour and tapioca significantly affected themoisture, ash, fiber, fat and protein contentsas well as sensory evaluation of meatballs. The best formulations was obtained on the meatballs was P2 with ratio banana excrescence flour and tapioca 1:2 which had a moisture content 68.34%, ash content 1.93%, fat content 0.81%, fiber content of 1.51% and protein content 12. 92%.The level of consumer preferences towards meatballs based on sensory descriptive and hedonic test of P2 treatment had a grayish-white color, aroma produced was somewhat fishy, had a taste the somewhat taste fishand texture of the resulting slightly chewy. Attributes color, aroma, flavor and texture of hedonic test gave the impression of a somewhat like. Keywords: meatball, banana excrescence, patin and quality